2009
DOI: 10.4081/818
|View full text |Cite
|
Sign up to set email alerts
|

Presence of atrial natriuretic factor in normal and hyperplastic human prostate and its relationship with oxytocin localisation

Abstract: In this work, we showed the presence of atrial natriuretic factor (ANF) in human prostate and compared its localisation in normal and hyperplastic conditions. ANF was localised in epithelial and stromal cells, being increased in hyperplasia, mainly in the stromal component. Moreover, we compared ANF and oxytocin positivity in the same glands, focusing on the possible relationship between the paracrine effects of these two hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…We hypothesize that Oxytocin exerts its role on these cells through an autocrine mechanism: the peptide is synthesized by HUVEC and acts on cell membrane Oxytocin receptors, starting the cascade of events that lead to NO production, release and finally to vasodilatation. Oxytocin is typically synthesized by the hypothalamus, but some authors have demonstrated that it can also be produced by other tissues, for example the prostate gland [26]. The Oxytocin protein and gene expression we detected in the endothelium of umbilical cord vessels is in agreement with these results, and suggests that this peptide may also be synthesized by endothelial cells.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 81%
“…We hypothesize that Oxytocin exerts its role on these cells through an autocrine mechanism: the peptide is synthesized by HUVEC and acts on cell membrane Oxytocin receptors, starting the cascade of events that lead to NO production, release and finally to vasodilatation. Oxytocin is typically synthesized by the hypothalamus, but some authors have demonstrated that it can also be produced by other tissues, for example the prostate gland [26]. The Oxytocin protein and gene expression we detected in the endothelium of umbilical cord vessels is in agreement with these results, and suggests that this peptide may also be synthesized by endothelial cells.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 81%
“…(1996) suggested that ANF may affect vasorelaxation because of a direct action of the molecule on vascular smooth muscle cells. ANF expression in other organs of male reproductive system has been reported by many authors (Mourdjeva et al., 2001; Farina‐Lipari et al., 2003). Through immunohistochemistry, we detected the presence of ANF peptide in rat seminal vesicles in the epithelium of the mucosa and the following RT‐PCR analysis on the whole seminal vesicle showed that ANF is synthesized by seminal vesicle cells.…”
Section: Discussionmentioning
confidence: 73%
“…Even if Ox is a peptide typically expressed in the hypothalamus, many authors have demonstrated that it can also be synthesized by other tissues, for example, the prostatic gland (Farina‐Lipari et al., 2003). Ox seems to play a role in male reproductive system functionality; it has been proposed to be involved in the modulation of testicular steroidogenesis and particularly in the conversion of testosterone (T) to dihydrotestosterone (DHT) (Nicholson et al., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…To date, it has been extensively studied the OT-induced inhibition of cell proliferation in ovarian carcinoma cells [5], breast cancer cells [6], neuroblastoma and glial tumors [7] and osteosarcoma [8]. Both pathologies are accompanied by alterations of OT, enhancing the importance of this paracrine factor that prostate synthesizes [1,14,15]. In human prostate, benign prostatic hyperplasia/hypertrophy (BPH) is a highly prevalent disorder that represents the most common cause of urinary obstruction in the ageing male population.…”
Section: Introductionmentioning
confidence: 99%